The role of family counseling in handling autistic children during at-home learning periods - Mujahid, Imam; Abdullah, Irwan; Minsih, Minsih; Muhamad, Siti Norlina (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2022)
The creation of good relations between family members during the COVID-19 pandemic is considered important to accommodate the learning needs of autistic children as during the pandemic, they are not able to learn optimally. This study aims to establish the role of family counseling in handling autistic children during at-home learning. The research uses a qualitative case study design. The informants were parents and core families of autistic children, and data collection involved interviews, observations, and documentation. The data analysis techniques employed were inductive analysis through reduction, data description, data coding, interpretation, and conclusions. The results show that the involvement of family members took place on a scheduled basis, relations between them improve, and making independent. The passion for building self-potential by developing a sense of respect for family members who help with autistic children's activities when learning from home. Family counseling through the involvement of family members can have a positive effect on the behavioral development of autistic children and a beneficial impact on other family members. The implication is that family counseling can be applied to help the social-emotional development of autistic children.